2011
DOI: 10.1089/bfm.2010.0088
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Intent to Breastfeed Exclusively? Breastfeeding Knowledge, Attitudes, and Beliefs in a Diverse Urban Population

Abstract: Background: Maternal knowledge and comfort with breastfeeding affect prenatal feeding intentions, and these intentions are strong predictors of feeding outcomes. However, predictors of exclusive breastfeeding intention have not been well characterized. Methods: We measured the association between intentions to exclusively breastfeed and knowledge of infant health benefits, feeding guidelines, and comfort related to breastfeeding in social settings. Participants were lower-income, ethnically diverse women in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 22 publications
9
101
1
5
Order By: Relevance
“…Interestingly, we found that the paternal role, foods to avoid, body change in mothers, mothers' health and methods to prolong breastfeeding would be important elements for the development of web-based educational information program. These findings agree with those of previous studies on the association between knowledge and attitudes toward breastfeeding [8,9,23].…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, we found that the paternal role, foods to avoid, body change in mothers, mothers' health and methods to prolong breastfeeding would be important elements for the development of web-based educational information program. These findings agree with those of previous studies on the association between knowledge and attitudes toward breastfeeding [8,9,23].…”
Section: Association Between Optimal Breastfeeding Practice and Totalsupporting
confidence: 93%
“…Also, previous studies have shown that maternal knowledge and attitudes toward breastfeeding may influence the personal decision and intention to breastfeed as well as the duration of breastfeeding [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Stuebe and Bonuck studied low-income women and discovered feeling more comfortable with public breastfeeding and increased knowledge regarding the benefits of breastfeeding were direct predictors of exclusive breastfeeding intention. [33] Similar results are reflected in this study, which demonstrated a decrease in public embarrassment of breastfeeding as more meetings were attended. The embarrassment of breastfeeding in public is a common reported barrier to breastfeeding especially in the adolescent population.…”
Section: Discussionsupporting
confidence: 85%
“…Maternal breastfeeding knowledge, attitudes, and confidence have been shown to be a strong predictor of the method of infant feeding. [28,33] Mossman and associates found a significant correlation between high prenatal confidence and initiation and duration of breastfeeding among adolescent mothers based on initial scores from the BAQ. [28] A more recent study regarding breastfeeding knowledge found a positive correlation between awareness of the World Health Organization's recommendation to exclusively breastfeed for 6 months and breastfeeding initiation and duration rates.…”
Section: Discussionmentioning
confidence: 99%
“…19 Finally, can be concluded that the woman's decision to breastfeed is a complex process that suffers influences of history of woman's life, of experiences of family and friends, demographic, cultural and social factors and also by her desire to breastfeed.…”
mentioning
confidence: 99%